ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK - Awalia, Fatma; Widaryanti, Widaryanti (STIE PENA, 2024)
This study aims to analyze the influence of managerial ownership, institutional ownership, independent board of commissioners, audit committee, and audit quality on tax avoidance. The independent variables used in this research are managerial ownership, institutional ownership, independent board of commissioners, audit committee, and audit quality, while the dependent variable is tax avoidance.This research utilizes secondary data obtained from annual reports. The population consists of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The sampling technique employed is purposive sampling, with a total sample size of 108 (3 years x 36 companies = 108). Data analysis methods include classical assumption tests, t-tests, and simultaneous tests, with the assistance of the SPSS program.The results of this study indicate that managerial ownership has a positive effect on tax avoidance. Meanwhile, institutional ownership, independent board of commissioners, audit committee, and audit quality have a negative effect on tax avoidance. The results also show that managerial ownership, institutional ownership, independent board of commissioners, audit committee, and audit quality collectively influence tax avoidance.